Data storage and management in Brazilian kidney transplant centers - Lobo, Clarissa Ferreira; Sandes-Freitas, Tainá Veras de (Brazilian Journal of Transplantation, 2019)
Purpose: This study investigated data storage and management by Brazilian kidney transplant (KT) centers. Methods: Cross-sectional study including all Brazilian KT centers enlisted in Registro Brasileiro de Transplantes / Associação Brasileira de Transplante de Órgãos and active in 2017 (n=124). An email was sent to those sites with a questionnaire including multiple choice questions. Results: From 124 KT centers, 28 (22.6%) answered the email. Most of them (39.3%) were located in the Southeast region of the country and were medium to high-volume transplant centers (67.9% performed >50 KT per year and 78.6% performed >500 KT since the beginning of the Program). Eighteen (64.3%) were public or non-profit hospitals and 26 (92.9%) were teaching hospitals. Fourteen (40%) sites used Microsoft Office Excel® spreadsheets as main database, 2 (7.1%) IBM-SPSS® spreadsheets, 3 (10.7%) used locally developed database systems, 2 (7.1%) used Collaborative Transplant Study-‘TaXi’ Database, 2 (7.1%) used other systems/software, and 5 (17.9%) had no tools for regular data management. Despite this, 67.9% published at least one paper in the last 2 years. Conclusion: Despite high percentage of teaching hospitals and scientific production, most of the investigated KT centers do not have centralized, structured and safety database management systems.